1997
DOI: 10.1002/(sici)1096-8628(19970711)71:1<111::aid-ajmg20>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral infarction in Noonan syndrome

Abstract: We report on an infant with severe Noonan syndrome, chylothoraces, and hepatosplenomegaly who suffered two episodes of cerebral infarction before age 6 months. No underlying cause for these events was found. The presentation is discussed in relationship to other reports of stroke in Noonan syndrome which have previously been associated with underlying vascular malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Hinnant [1995] reported a 15-year-old girl with thromboembolic infarcts and probable hypoplasia of the posterior cerebral vessels. In addition, Robertson et al [1997] reported a 10-month-old boy with no structural cerebral abnormality who suffered two episodes of cerebral infarction. There have been no reports mentioning cavernous hemangioma occurring in NS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hinnant [1995] reported a 15-year-old girl with thromboembolic infarcts and probable hypoplasia of the posterior cerebral vessels. In addition, Robertson et al [1997] reported a 10-month-old boy with no structural cerebral abnormality who suffered two episodes of cerebral infarction. There have been no reports mentioning cavernous hemangioma occurring in NS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Costello syndrome can cause growth failure, intellectual disability, and dysmorphic facial features in addition to other skin and musculoskeletal anomalies. There is no known association between Costello syndrome and stroke, though related disorders Noonan and Neurofibromatosis 1, which also affect the Ras signaling pathway, have been reported with stroke (Robertson et al, 1997; Rukavina et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Costello syndrome can cause growth failure, intellectual disability, and dysmorphic facial features in addition to other skin and musculoskeletal anomalies. There is no known association between Costello syndrome and stroke, though related disorders Noonan and Neurofibromatosis 1, which also affect the Ras signaling pathway, have been reported with stroke[11, 12].…”
Section: Resultsmentioning
confidence: 99%